Development of quantitative quality cost matrix for Malaysian construction quality management system - Che Ali, Mukhtar (2010)
One of the key areas being emphasized in ISO 9001 Quality Management System (QMS) is performance measurement towards achieving continual improvement. Currently most of the quality performance indicators devised by ISO 9001 certified contractors are the physical parameters such as list of defects, number and category of nonconformances (NCR), number of customer complaints and scoring from customer feedback forms. However, these parameters are unable to be linked with the project cost performance. In view of the problem this research is carried out with the aim to develop a measurement tool that can be used to measure the project quality performance by ISO 9001 certified contractors with respect to cost. The objectives of the research are to evaluate the current knowledge and practice on quality cost, to identify construction activities affecting quality, and to develop the quality cost matrix that can serve as an effective tool to analyze quality cost in construction projects. The research was carried out in four distinct stages and employed two main instruments of data collection i.e. questionnaire survey and semi-structured interview with the experts. The results from the exploratory survey revealed that lack of knowledge on quality cost prevails among the project management team. This leads to low practice of quality cost in our construction industry. However, majority of the respondents agreed that quality cost can be a good quality performance indicator. The proposed quality cost matrix utilized the Preventive Appraisal Failure (PAF) model. Based on the results from the survey and semi-structured interviews a quality cost matrix that tailored to the local working environment was developed. The breakdown of the main components in the matrix is in accordance to QLASSIC basic assessment structure i.e. structural, architectural, M & E, and external work. In addition this matrix also includes other failure cost which comprises of wastage of material, Liquidated and Ascertain Damages (LAD), regulatory penalty, and miscellaneous expenditure. In terms of causes of failure the research has grouped failures into four Ms i.e. material, method, machine and man. The developed matrix was validated through special focus group workshop which consisted of experts from the quality consultancy companies. One of the significant contributions from this research is that the quality cost matrix can be used to measure the effectiveness of the established quality plan for a given project. Furthermore the output of the research would enable to improve on data analysis by ISO 9001 certified contractors